PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA MIE GACOAN DI SEMARANG - Andikawati Andikawati; Siti Nur Virda; M. Rifki Bakhtiar (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The rapid growth of the culinary business has increased competition among food and beverage companies. Customer satisfaction has become an important factor in maintaining customer loyalty and business sustainability. This study aims to analyze the effect of service quality and price on customer satisfaction at Mie Gacoan in Semarang. The research uses a quantitative approach with data collected through questionnaires distributed to consumers who have purchased products at Mie Gacoan Semarang. The sampling technique used is purposive sampling. Data analysis was conducted using multiple linear regression analysis. The results indicate that service quality has a positive and significant effect on customer satisfaction. Price also has a positive and significant effect on customer satisfaction. Simultaneously, service quality and price significantly influence customer satisfaction. These findings suggest that improving service quality and maintaining competitive prices can increase customer satisfaction and strengthen the competitive position of Mie Gacoan in the culinary industry.